Use of an electronic medication management application to support Pharmacists Review to Optimise Medicines in Residential Aged Care (PROMPT-RC): a study protocol for a parallel cluster randomised controlled trial - Kenneth Lee; Dennis Petrie; Dee Mangin; Christopher Etherton-Beer; Amy Theresa Page; Esa Y H Chen; Nagham Ailabouni; Liza Seubert; Rhonda Marise Clifford; Kathleen Potter; Nahal Mavaddat; Sarah Hosking; et al. (BMJ Open)
Introduction Most older adults living in residential aged care facilities (RACFs) have at least one marker of potentially suboptimal prescribing. Pharmacists play a crucial role in medication management, with their effectiveness enhanced by using computerised decision support tools. The Pharmacists Review to Optimise Medicines in Residential Aged Care (PROMPT-RC) study aims to optimise medicine use by providing pharmacists in RACFs with an electronic medicine management app with integrated decision support (AusTAPER App/Pathway) to use as part of medication reviews they undertake.Methods and analysis The PROMPT-RC study is a parallel cluster randomised controlled trial design involving Australian RACFs. It will assess if pharmacists’ use of the AusTAPER App/Pathway for medication reviews improves medication regimens for RACF residents compared with usual care. Pharmacists in RACFs randomised to the intervention arm will be trained to use the AusTAPER App/Pathway, which flags potentially inappropriate medicines (PIMs) across a person’s entire medicine regimen. Pharmacists in RACFs randomised to the control arm will not have access to the AusTAPER App/Pathway—they will continue to provide usual care. The primary outcome is the difference in the number of regular medicines between treatment arms at 12 months. Secondary outcomes will measure the number of regular and pro re nata medicines, PIMs, medicine administration times, medicine regimen complexity, use of antipsychotics, antidepressants, and benzodiazepines, quality of life, mortality, instances of physical restraint, and the number of falls, hospitalisations and general practitioner/health professional visits. The cost-effectiveness of the AusTAPER App/Pathway compared with usual care will be calculated. Data collection will occur at baseline, 3, 6, 9 and 12 months postrandomisation and 3 and 6 months prebaseline. We aim to recruit 668 participants to adjust for an estimated 10% loss to follow-up, giving 334 participants in each arm. Data analysis will follow an intention-to-treat approach using a linear mixed model.Ethics and dissemination Ethical approval was obtained from The University of Western Australia Human Research Ethics Committee (Reference: 2024/ET000525; approved 14 August 2024). Reciprocal approval was also obtained in other states. This study is registered on the Australian New Zealand Clinical Trials Registry (https://anzctr.org.au). Trial findings will be disseminated through national and international peer-reviewed publications and conferences.Trial registration number ACTRN12624001409561.